Higher Levels and Intensity of Physical Activity Are Associated with Reduced Mortality among Community Dwelling Older People - Eva Hrobonova; Elizabeth Breeze; Astrid E. Fletcher (Journal of Aging Research)
Introduction. There is limited evidence on physical activity and mortality in older people. Methods. People aged 75–84 years (n = 1449) participating in a randomized trial of health screening in UK general practice were interviewed about their physical activity (PA) and were assessed for a wide range of health and social problems. Mortality data were collected over 7 years of followup. Results. Full information on PA and potential confounders was available in 946 people. Those in the highest third of duration of PA had a lower mortality, confounder-adjusted Hazard Ratio (HR) = 0.74, and 95% Confidence Interval (CI) 0.56–0.97, compared to the lowest third. Similar benefits were seen when categorized by intensity of PA, with those in the highest group having a lower mortality, confounder-adjusted HR = 0.61, and 95% CI 0.47–0.79, compared to the lowest category. Conclusions. Our results suggest the importance of providing older people with opportunities for physical activity.